Negotiated Syllabus on General English Course at University Level: Adjusting between Students’ Need and Learning Goals - Sepyanda, Marsika; Syarif, Hermawati; Zainil, Yetty (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Negotiated syllabus refers to syllabus which is designed based on discussion about how learning and instruction are arranged and carried out in the classroom that will be decided by the lecturers and students. It is important to have negotiated syllabus because there are many problems may be found related to syllabus that has already designed earlier. It needs to adjust the syllabus with things that the students actually need on their learning. Moreover, English is learnt by various students at university level as general course which comprehend their language ability in form of communicative and educational purposes. The students probably have different ability and background knowledge about English as foreign language. They also have various purposes in learning English as a course in university level. Therefore, this essay aims to investigate the benefits and drawbacks of negotiated syllabuses in general English courses, where they can be viewed from two different sides. First, it is considered based on students’ need which are various because of their background knowledge and basic language ability. Second, it is viewed from learning goals as the main target of a lecturer in designing a course. Therefore, negotiated syllabus is needed to be implemented in conducting general English courses even it has advantages and disadvantages on the implementation progress.